Chaotic Behavior and Subharmonic Bifurcations for the Duffing-Van Der Pol Oscillator (Journal of Nonlinear Modeling and Analysis, 2024)
Chaotic behavior for the Duffing-van der Pol (DVP) oscillator is investigated both analytically and numerically. The critical curves separating the chaotic and non-chaotic regions are obtained. The chaotic features on the system parameters are discussed in detail. The conditions for subharmonic bifurcations are also obtained. Numerical results are given, which verify the analytical ones.